Implementation of Discipline Character Values in Grade 4A Students at Elementary School: Implementasi Nilai Karakter Disiplin Pada Siswa Kelas 4A di SD - Livia Medi Marthasari; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2022)
The research used is descriptive qualitive research. Aims to knowing the value of dicipline character in grade 4a students at SD Muhammadiyah 2 Sidoarjo. Technique data collection using interview techniques, observation, and documentation with analytical techniques data 1) data reduction 2) data presentation 3) drawing conclusions that are tested for the validity of the data by using sourch triangulation. The results showed that the application of students discipline character values had been realized through the rules and habits of students carried out at school with various activities in the form of 1) routine activities 2) spontaneous activities 3) conditioning activities and 4) exemplary activities. In these activities, grade 4A students’ can run implementation of the four aspects compiled by researchers.